IAU Focus Meeting 7: Stellar Physics in Galaxies throughout the Universe. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Leitherer, Claus; Charlot, Stéphane; Maraston, Claudia
Abstract: A 3-day Focus Meeting entitled "Stellar Physics in Galaxies throughout the Universe" was held during the IAU XXIX General Assembly. The meeting brought together astrophysicists from the stellar physics, extragalactic astrophysics and cosmology communities to discuss how current and future results can foster progress in these disjoint science areas. Areas covered include stellar evolution of single and binary stars from the zero-age main-sequence to the terminal stage, the feedback of stars to the interstellar medium via radiation, dust production and chemical enrichment, and the properties of the most massive stars and of cosmologically significant stellar phases such as AGB and Wolf-Rayet stars. The limitations of our understanding of the physics of local stars and their effects on, e.g., ages, chemical composition and the initial mass function of galaxies at low to high redshift were evaluated.